Functional alteration patterns of default mode networks: comparisons of normal aging, amnestic mild cognitive impairment and Alzheimer's disease. Issue 12 (16th June 2013) - Cha, Jungho; Jo, Hang Joon; Kim, Hee Jin; Seo, Sang Won; Kim, Han‐Soo; Yoon, Uicheul; Park, Hyunjin; Na, Duk L.; Lee, Jong‐Min
Abstract Most default mode network (DMN) studies in patients with amnestic mild cognitive impairment (aMCI) and Alzheimer's disease (AD) are based on the comparison of only two groups, namely patients and controls. Information derived from comparing three groups, normal, aMCI and AD, simultaneously may lead us to better understand the progression of dementia. The purpose of this study was to evaluate functional connectivity of DMN in the continuum from normal through aMCI to AD. Differences in functional connectivity were compared between the three groups using independent component analysis. The relationship between functional connectivity and disease progression was investigated using multiple regression analysis with Mini‐Mental State Examination (MMSE) scores. The results revealed differences throughout the left posterior cingulate cortex (PCC), left middle temporal gyrus (MTG), right middle frontal gyrus (MFG) and bilateral parahippocampal gyrus (PHG). Both patients with aMCI and those with AD showed decreased connectivity in the left PCC and left PHG compared with healthy subjects. Furthermore, patients with AD also showed decreased connectivity in the left MTG and right PHG. Increased functional connectivity was observed in the right MFG of patients with AD compared with other groups. MMSE scores exhibited significant positive and negative correlations with functional connectivity in PCC, MTG and MFG regions. Taken together, increased functional connectivity in the MFG for AD patients might compensate for the loss of function in the PCC and MTG via compensatory mechanisms in corticocortical connections.